Current Topics in Anesthesiology - Hakan Erbay, Riza (IntechOpen, 2017)
Throughout the history of thousands of years of medicine, it felt a great need to anesthesia for surgical operations, and only in 1846, Morton's introduction of ether anesthesia began scientific anesthesiology. Today, as technological developments and knowledge have increased, the practices of anesthesiology are becoming increasingly sophisticated. In this book, current drugs and applications for anesthesiology as well as new developments for the use of ultrasonography are presented.